Implementation of a project management dashboard in an E-commerce company - Brunassi, Vitor Ruiz; Campanini, Luciano; Fernandes, Sânia da Costa (Brazilian Journal of Production Engineering, 2026)
With the growth of e-commerce, continuous improvement projects are essential for enhancing operations. This work aims to develop a Business Intelligence (BI) dashboard to improve project management, providing greater efficiency in monitoring initiatives and visibility for stakeholders. To this end, the research methodology used was action research, which allowed for the identification of practical needs, the collection of relevant data, and the implementation of a solution directly within the organizational environment, ensuring that the tool met the specific demands of the study area. The project management BI dashboard centralized information that was previously scattered across spreadsheets, providing greater organization and standardization of project data. Furthermore, the tool improved the visualization of strategic indicators, such as project status, resolution time, and progress, allowing for real-time monitoring. Key results included improved operational efficiency and data-driven decision-making. The developed solution facilitated communication with leadership and key stakeholders through structured reports and insights, contributing to greater agility in decision-making processes.
Keywords: Business intelligence; project management; action research; e-commerce; dashboard